2022
DOI: 10.21203/rs.3.rs-2376536/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of simulated fire and browsing on the resprouting of subtropical dune thicket shrubs in the southeastern Cape Floristic Region

Abstract: Aim: The expansion of subtropical thicket vegetation at the expense of more species-rich, fire-prone fynbos, potentially due to lower frequency and severity of fire and browsing, is a concern in many coastal dune landscapes of the Cape Floristic Region (CFR) where these two vegetation types co-occur. We were interested in the effects of severe fire and browsing treatment on the vigour of post-fire resprouts of dune thicket shrubs. Location: Cape St Francis, CFR, South Africa. Methods: We used an in-situ experi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
1
1
0
Order By: Relevance
“…We found evidence of plant size increasing post-fire resprouting vigour in all species in this study, potentially due to increased resources in larger plants promoting quicker growth following fire. Similar evidence of vigour increasing with plant size has been found following fire and coppicing for resprouting individuals in intact ecosystems (Casals et al, 2018;Moreira et al, 2012;Strydom et al, 2023).…”
Section: Plant Size Influenced Survival and Vigour But Not Resproutin...supporting
confidence: 70%
See 1 more Smart Citation
“…We found evidence of plant size increasing post-fire resprouting vigour in all species in this study, potentially due to increased resources in larger plants promoting quicker growth following fire. Similar evidence of vigour increasing with plant size has been found following fire and coppicing for resprouting individuals in intact ecosystems (Casals et al, 2018;Moreira et al, 2012;Strydom et al, 2023).…”
Section: Plant Size Influenced Survival and Vigour But Not Resproutin...supporting
confidence: 70%
“…Conversely, we found that survival increased with plant size for three species (although not significantly for two species). In forest stands in Mediterranean Iberia (Casals et al., 2018) and thickets in South Africa (Strydom et al., 2023), post‐fire resprouting success was higher in larger plants, or resprouting success varied with plant size (Giddey et al., 2022).…”
Section: Discussionmentioning
confidence: 99%